Pengaruh Gaya Kepemimpinan dan Disiplin Kerja Terhadap Kinerja Karyawan di PT. Presisi Kurnia Makmur Cileungsi - Saputri, Erin Indah Bella; Z, Zahra; Rosihana, Athiy Dina (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to analyze the effect of leadership style and work discipline on employee performance at PT. Presisi Kurnia Makmur Cileungsi. The research employed a quantitative approach with an associative method. The population consisted of 36 employees in the production division, all of whom were taken as samples using a saturated sampling technique. Data were collected using a Likert-scale questionnaire and analyzed with SPSS version 25. The validity and reliability tests confirmed that the research instrument was appropriate, while the classical assumption tests (normality, multicollinearity, and heteroscedasticity) indicated that the data met the requirements for regression analysis. Multiple linear regression results showed that: (1) leadership style has a positive and significant effect on employee performance with a t-value of 3.028, a significance level of 0.005, and a regression coefficient of 0.386; (2) work discipline has a positive and significant effect with a t-value of 4.166, a significance level of 0.000, and a regression coefficient of 0.590; and (3) simultaneously, both variables significantly influence employee performance with an F-value of 40.165, a significance level of 0.000, and an R² of 0.709. The findings highlight the importance of implementing a communicative and motivational leadership style along with consistent discipline enforcement through clear rules, effective supervision, and balanced rewards to enhance employee performance.